2018
DOI: 10.1097/aud.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Voice Pitch and Vocal-Tract Length in Cochlear Implant Users

Abstract: Objectives:When listening to two competing speakers, normal-hearing (NH) listeners can take advantage of voice differences between the speakers. Users of cochlear implants (CIs) have difficulty in perceiving speech on speech. Previous literature has indicated sensitivity to voice pitch (related to fundamental frequency, F0) to be poor among implant users, while sensitivity to vocal-tract length (VTL; related to the height of the speaker and formant frequencies), the other principal voice characteristic, has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(145 citation statements)
references
References 82 publications
9
136
0
Order By: Relevance
“…For the bimodal CI+HA users, residual acoustic hearing in the HA ear allows the separation of different voice pitches due to better encoding of spectral information than in the CI ear. In contrast, bilateral CI users, who lack an acoustic hearing ear, have less access to this cue and have difficulty discriminating voice gender (Cleary and Pisoni, 2002;Fu et al, 2005;Gaudrain and Başkent, 2018). The way the CI processor is programmed does not provide sufficient spectral resolution to distinguish F 0 and thus gender.…”
Section: Speech Release From Masking In Nh and Hi Listenersmentioning
confidence: 99%
“…For the bimodal CI+HA users, residual acoustic hearing in the HA ear allows the separation of different voice pitches due to better encoding of spectral information than in the CI ear. In contrast, bilateral CI users, who lack an acoustic hearing ear, have less access to this cue and have difficulty discriminating voice gender (Cleary and Pisoni, 2002;Fu et al, 2005;Gaudrain and Başkent, 2018). The way the CI processor is programmed does not provide sufficient spectral resolution to distinguish F 0 and thus gender.…”
Section: Speech Release From Masking In Nh and Hi Listenersmentioning
confidence: 99%
“…Furthermore, while normal-hearing listeners make use of both GPR and VTL differences for 541 talker sex categorization, CI users seem to rely exclusively on differences in GPR (Fuller et al,542 2014; Meister et al, 2016) which has been attributed to their limited access to VTL cues 543 (Gaudrain and Başkent, 2018). 544…”
Section: Implications For Cochlear-implant Users 533mentioning
confidence: 99%
“…Both analysis and synthesis filters were given the same filter order for a given condition. This choice of filter orders was based on data from Gaudrain and Başkent (2015), which showed that shallower filters, simulating larger channel interaction, yielded VTL JNDs that were close to those obtained from actual CI users (Gaudrain and Başkent, 2018). It is expected that frequency shift might play a larger role with sharper filters than with shallower filters because shallow filters effectively become more similar to each other, which should manifest as an interaction effect between filter order and frequency shift.…”
Section: Analysis Filtersmentioning
confidence: 99%
“…It is expected that frequency shift might play a larger role with sharper filters than with shallower filters because shallow filters effectively become more similar to each other, which should manifest as an interaction effect between filter order and frequency shift. In experiments 2 and 3, 16 analysis filter bands of 12th-order were used instead because pilot data revealed that 4th-and 8th-order filters, when combined with the synthesis filter models used in experiment 3, yielded unrealistically large VTL JNDs compared to those of actual CI users (Gaudrain and Başkent, 2018).…”
Section: Analysis Filtersmentioning
confidence: 99%
See 1 more Smart Citation